D정수장 정밀여과막 실증플랜트의 최적 운전조건 연구 - 양형재(Hyung-Jae Yang); 이승훈(Seung-Hoon Yi); 문경란(Kyung-Ran Moon) (Daehan hwan'gyeong gonghag hoeji, 2017)
Membrane filtration has become more popular in drinking water treatment recently, since the filtration can control not only particulate matters but also pathogenic microorganisms such as giardia and cryptosporidium very effectively. Pilot-scale ($120m^3/d$ of treatment capacity) and test-bed ($25,000m^3/d$ of treatment capacity) microfiltration experiments were conducted to find optimum operating mode and the critical flux. Optimum operating mode of pilot-test was assessed as inflow 1.0 min, filtration 36.5 min, air backwash 0.9 min, backwash 1.0 min and outflow 1.0 min with 50 LMH ($L/min{·}m3^$) of critical flux. Critical Flux was calculated to be $50L/m^2-h$ (within TMP 0.5 bar) based on the increase formula of the transmembrane pressure difference according to the change of time at Flux 20, 40, 56 and 62 LMH in pilot operation. Chemical cleaning was first acid washed twice, and alkali washing was performed secondarily, and a recovery rate of 95% was obtained in the test-bed plant. The results of operating under these appropriate conditions are as follows. Turbidity of treated water were 0.028, 0.024, 0.026 and 0.028 NTU in spring, summer, autumn and winter time, respectively. Microfiltration has superior treatment capability and performance characteristics in removing suspended solids and colloidal materials, which are the main cause of turbidity and important carrier of metal elements, and it has shown great potential in being an economically substitute to traditional processes (sand filtration). 최근 막여과 공정은 입자상 물질뿐만 아니라 Giardia, cryptosporidium과 같은 병원성미생물이 효과적으로 제거됨에 따라 국내외 적용성이 확대되는 추세이다. 본 연구는 광주광역시 D정수장의 원수 침전상등수의 처리를 위해 $120m^3/d$ 처리규모의 Pilot Plant (2014. 1월부터 운영)와 $2,500m^3/d$ 처리규모의 실증실험시설(2015. 1월부터 운영)의 막여과 공정을 운영하면서 최적 운전조건과 한계여과속도를 찾고자 하였다. 정밀여과막의 Pilot-test에서 얻어진 운전모드는 유입 1.0분, 여과 36.5분, 공기역세 0.9분, 역세 1.0분, 배출 1.0분이었으며, 이를 적용하여 실증실험을 하였다. 한계여과속도(critical flux)는 Pilot 운전에서 Flux 20, 40, 56 및 62 LMH일 때의 시간의 변화에 따른 막간차압의 증가식을 기반으로 $50L/m^2-h$로 산정(TMP 0.5bar 이내)되었다. 화학세정은 1차로 산세정 2회, 2차로 알칼리 세정을 하여 95%의 회복율을 얻었다. 이러한 적정 조건으로 운전한 결과 처리수의 탁도는 봄 여름 가을 겨울 평균 각각 0.028, 0.024, 0.026 및 0.028 NTU, 연평균 탁도는 0.026 NTU로, 탁도 제거율은 98.4%로 나타났다. 광주광역시 D정수장의 원수 침전상등수를 1일 $2,500m^3$ 처리하는 실증실험시설 운영을 통해 부유고형물 및 콜로이드성 물질을 제거하는데 탁월한 처리성능을 확인하였고, 일반적인 모래여과공정을 대체할 수 있는 적정운영기술이 확보되었다.